Production, crystallization and preliminary X-ray crystallographic studies of the bacteriophage phi 12 packaging motor. - Mancini, E; Kainov, D; Wei, H; Gottlieb, P; Tuma, R; Bamford, D; Stuart, D; Grimes, J (2004)
The hexameric ATPase P4 from bacteriophage phi 12 is responsible for packaging single-stranded genomic precursors into the viral procapsid. P4 was overexpressed in Escherichia coli and purified. Crystals of native and selenomethionine-derivatized P4 have been obtained that belong to space group I222, with half a hexamer in the asymmetric unit and unit-cell parameters a = 105.0, b = 130.5, c = 158.9 A. A second crystal form of different morphology can occur in the same crystallization drop. The second form belongs to space group P1, with four hexamers in the asymmetric unit and unit-cell parameters a = 114.9, b = 125.6, c = 153.9 A, alpha = 90.1, beta = 91.6, gamma = 90.4 degrees. Synchrotron X-ray diffraction data have been collected for the I222 and P1 crystal forms to 2.0 and 2.5 A resolution, respectively.